Commitment in symmetric contests - Possajennikov, Alex (Economics Bulletin, 2009)
The paper proves that in two-player logit form symmetric contests with concave success function, commitment to a particular strategy does not increase a player's payoff, while in contests with more than two players it does. The paper also provides a contest-like game in which commitment does not increase a player's payoff for any number of players.